2021
DOI: 10.14309/ctg.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fecal Immunochemical Testing Levels With Pathology Results in a National Colorectal Cancer Screening Program

Abstract: INTRODUCTION: Fecal immunochemical testing (FIT) positivity is determined by a threshold decided by individual screening programs. Data are limited on correlation between FIT levels and pathology identified at colonoscopy. Our aim was to examine the correlation between FIT levels and pathology identified in a national colorectal cancer screening program. METHODS: FIT levels (n = 9,271) were analyzed and correlated with patient demographics and pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Seventyfive full-length articles were assessed for inclusion and 23 studies were included in the final analysis [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. Sixteen studies reported SSPDR after only FIT testing [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34], three reported SSPDR on both FIT and FIT-DNA [35,36,37], and three studies reported SSPDR after only FIT-DNA testing (▶ Fig. 1) [38,39,40,41].…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%
“…Seventyfive full-length articles were assessed for inclusion and 23 studies were included in the final analysis [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. Sixteen studies reported SSPDR after only FIT testing [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34], three reported SSPDR on both FIT and FIT-DNA [35,36,37], and three studies reported SSPDR after only FIT-DNA testing (▶ Fig. 1) [38,39,40,41].…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%
“…The findings were also reproduced by the Austrian researchers (3). This is interesting, as FIT level is associated with adenoma size (27). Secondly, adherence to surveillance is crucial, and FIT may make up a first option for patients who hesitate to undergo colonoscopy or bowel cleansing for psychological reasons, for patients with severe comorbidity, or for those living far away from nearest endoscopy unit (28).…”
Section: Discussionmentioning
confidence: 99%